2009
DOI: 10.1016/j.juro.2009.07.044
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Risk Factors for Nephrolithiasis After Roux-en-Y Gastric Bypass Surgery

Abstract: Our prospective study demonstrated multiple factors that increase the relative risk of nephrolithiasis after Roux-en-Y gastric bypass. These changes may make stone formation after Roux-en-Y gastric bypass increasingly likely and pose an ongoing challenge in the realm of urology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 14 publications
5
38
0
Order By: Relevance
“…The prevalence rate of hyperoxaluria after BS (20%) in our study agrees closely with the rate reported by Duffey et al (8) (29%), but was lower than the rates reported by other studies, which reached values as high as 74% (5,(9)(10)(11)(12). On the other hand, the current mean oxalate excretion values were similar to those reported by other investigators (7,8,11). The highly variable degree of secondary hyperoxaluria may be due to differences in protein, lipid, calcium, and oxalate intake from other studies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The prevalence rate of hyperoxaluria after BS (20%) in our study agrees closely with the rate reported by Duffey et al (8) (29%), but was lower than the rates reported by other studies, which reached values as high as 74% (5,(9)(10)(11)(12). On the other hand, the current mean oxalate excretion values were similar to those reported by other investigators (7,8,11). The highly variable degree of secondary hyperoxaluria may be due to differences in protein, lipid, calcium, and oxalate intake from other studies.…”
Section: Discussionsupporting
confidence: 90%
“…It may also have occurred because calcium supplements were withdrawn 3 days before urine collection in our study. Hypomagnesuria was not frequent in our series of post-BS patients, which was also the case in several other studies (5,7,(9)(10)(11)(12). This is most likely because magnesium depletion is more commonly due to diarrhea, which was detected in only two post-BS patients (one RYGB and one BD-DS).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Some detailed analyses of the hyperoxaluria occurring after bariatric surgery have been performed by measuring urinary oxalate excretion in 24-h urine collections [9][10][11][12][13][14][15][16]. Duffey et al [10,11] conducted a long-term prospective study of the hyperoxaluria after R-Y gastric bypass, and revealed that the postoperative mean urinary oxalate excretion was significantly elevated from baseline at 3 months, and continued to grow in magnitude, reaching a stable level 1-2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%